Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2470700
|View full text |Cite
|
Sign up to set email alerts
|

Digital motherhood

Abstract: New mothers can experience social exclusion, particularly during the early weeks when infants are solely dependent on their mothers. We used ethnographic methods to investigate whether technology plays a role in supporting new mothers. Our research identified two core themes: (1) the need to improve confidence as a mother; and (2) the need to be more than 'just' a mother. We reflect on these findings both in terms of those interested in designing applications and services for motherhood and also the wider CHI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(48 citation statements)
references
References 18 publications
2
43
0
3
Order By: Relevance
“…On a mundane level, the capacity to capture a virtually unlimited number of family snapshots at, effectively, zero cost and share them in a single step via social media has removed the need to expensively print and distribute photographs [9] to share with close family and friends. Perhaps more profound is the capacity for social media to elicit responses from such close family which can confirm that 'good parenting' is taking place [27,43]. The sharing of digital snapshots can also be used to gain support from weaker-tie networks, in addition to immediate friends and family [52].…”
Section: Introductionmentioning
confidence: 99%
“…On a mundane level, the capacity to capture a virtually unlimited number of family snapshots at, effectively, zero cost and share them in a single step via social media has removed the need to expensively print and distribute photographs [9] to share with close family and friends. Perhaps more profound is the capacity for social media to elicit responses from such close family which can confirm that 'good parenting' is taking place [27,43]. The sharing of digital snapshots can also be used to gain support from weaker-tie networks, in addition to immediate friends and family [52].…”
Section: Introductionmentioning
confidence: 99%
“…Alongside a multi-generational perspective that considers the long-term sustainability of technology [18], it is argued there is great potential in studying key transition periods in a lifespan to critically consider our changing digital behaviors and values held in Internet-enabled technologies [2]. Therefore, HCI research has recently considered key events in technology users' lives, such as 'coming of age' [45,61], marriage [36], becoming a parent [22], relationship break-ups [57], divorce [40], and death and memorialization [37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study found that white postnatal women in the UK are less at risk of developing postnatal depression and personality dysfunction when living in areas with a higher density of their own ethnic group (Du Preez et al 2016). Gibson and Hanson (2013) observe that UK mothers consider Facebook an important aspect of their motherhood because it allows them to be socially connected (see also Kaufmann, Buckner, and Ledbetter 2017). A randomised controlled trial suggested that support of lay workers improves maternal and child outcomes in disadvantaged families (Kenyon et al 2016).…”
Section: Parenting Challenges and Life Chancesmentioning
confidence: 99%